POTRET PEREMPUAN DALAMRANAH POLITIK DI INDONESIA - Sarifa Suhra (Institut Agama Islam Negeri (IAIN) Bone-Indonesia, 2018)
This paper examines the portrait of women in the realm of politics in Indonesia, using qualitative descriptive, then the analysis of the results showed that the involvement of women in the realm of politics in Indonesia, recorded significant gains the names of women who contribute in political activity both before and after Indonesia became independent from the era of the Kingdom until it formed into independent and sovereign. A physical struggle against colonizers have capture names such as Cut Nyak Dien, Martha Tiahahu, Yolanda Maramis and so on. In the emerging national movement name Rasuna Said and Trine. While RA Kartini, Dewi Sartika and had carved their names as people who fought for the rights of women to acquire education and position in the realm of political equals with men. The new order era and the era of reform has broadened the way for women to be actively engaged in all aspects of life including politics.Various forms of political struggle was the Group of women, such as Parliament, the Cabinet, political parties, NGOs, and so on. In Indonesia it is generally the involvement of women in politics is quite high and significant proven in the election of regional heads in unison 2018 women win many politicians both at the level of the Governor and Governor or mayor.